A rare case report of a primary lung cancer comprising adenocarcinoma and atypical carcinoid tumor, with the carcinoid component harboring EML4-ALK rearrangement - Hu, Wenbin; Zhao, Jiaming; Wang, Guoxia; Wang, Qihao; Deng, Mingming; Shen, Jie; Hofman, Paul; Urbanska, Edyta Maria; Santoni-Rugiu, Eric; Christopoulos, Petros; Ramirez, Robert A.; Hida, Toyoaki; et al. (Translational Lung Cancer Research, 2024)
Background: The occurrence of pulmonary adenocarcinoma coexisting with atypical carcinoid tumors is a rare phenomenon. The presence of EML4-ALK fusion in an atypical carcinoid component of a histologically mixed tumor is even more uncommon. Due to their infrequency, the origin and pathogenesis of these mixed tumors remain largely unknown. The advances of therapy development in such patients are still limited and there is no standard treatment. We present a case of collision tumor in the lung consisting of atypical carcinoid and adenocarcinoma to better understand the clinical characteristics of this disease. Case Description: We report an extremely rare case of EML4-ALK rearrangement in a pulmonary atypical carcinoid tumor that coexisting with adenocarcinoma. A 58-year-old woman, who was asymptomatic, underwent pulmonary lobectomy due to the detection of a gradually enlarging solitary pulmonary nodule in the right upper lung. Histological examination of the resected tumor revealed the presence of both atypical carcinoid (approximately 80%) and adenocarcinoma (approximately 20%) components. Metastases by the carcinoid component were observed in mediastinal lymph nodes (station 2R and 4R) and in the primary tumor. Anaplastic lymphoma kinase (ALK) rearrangement was detected in both the primary and metastatic lesions of the carcinoid tumor. Four cycles of chemotherapy with etoposide and carboplatin were dispensed after surgery. Conclusions: This is the first reported case of coexisting pulmonary adenocarcinoma and atypical carcinoid tumor with an ALK fusion only detected in the carcinoid component. The presence of ALK rearrangement in pulmonary carcinoid tumor is very uncommon, and there is currently no standard treatment for advanced stages. Therefore, comprehensive molecular testing, including ALK rearrangement analysis, should be recommended for mixed tumors exhibiting features of atypical carcinoid. ALK inhibitors could represent a potential treatment strategy for selected patients.